Zeolite as slow release fertilizer on spinach yields and quality in a greenhouse test - Li, Zhaohui; Zhang, Yingpeng; Li, Yan (Journal of plant nutrition, 2013)
There has been a great need to reduce the non-point source pollution due to pesticide and fertilizer applications. With a high surface area and large cation exchange capacity, zeolite was proposed to use as carriers to control ammonium and potassium release. A greenhouse test was conducted to evaluate spinach growth and spinach quality after application of zeolite pre-load with ammonium (NH₄⁺) and potassium (Eco-zeolite). An increase in spinach yield with comparable vitamin C content was achieved using the Eco-zeolite. However, elevated oxalate content was unexpected, possible due to the presence of NH₄⁺ as the exchangeable cations after modification.